Stress-associated neurobiological activity associates with the risk for and timing of subsequent Takotsubo syndrome. (26th March 2021) - Radfar, Azar; Abohashem, Shady; Osborne, Michael T; Wang, Ying; Dar, Tawseef; Hassan, Malek Z O; Ghoneem, Ahmed; Naddaf, Nicki; Patrich, Tomas; Abbasi, Taimur; Zureigat, Hadil; Jaffer, James; et al.
Abstract: Aims: Activity in the amygdala, a brain centre involved in the perception of and response to stressors, associates with: (i) heightened sympathetic nervous system and inflammatory output and (ii) risk of cardiovascular disease. We hypothesized that the amygdalar activity (AmygA) ratio is heightened among individuals who develop Takotsubo syndrome (TTS), a heart failure syndrome often triggered by acute stress. We tested the hypotheses that (i) heightened AmygA precedes development of TTS and (ii) those with the highest AmygA develop the syndrome earliest. Methods and results: Individuals ( N =104, median age 67.5 years, 72% female, 86% with malignancy) who underwent clinical 18 F-FDG-PET/CT imaging were retrospectively identified: 41 who subsequently developed TTS and 63 matched controls (median follow-up 2.5 years after imaging). AmygA was measured using validated methods. Individuals with (vs. without) subsequent TTS had higher baseline AmygA ( P =0.038) after adjusting for TTS risk factors. Further, AmygA associated with the risk for subsequent TTS after adjustment for risk factors [standardized hazard ratio (95% confidence interval): 1.643 (1.189, 2.270), P =0.003]. Among the subset of individuals who developed TTS, those with the highest AmygA (>mean + 1 SD) developed TTS ∼2 years earlier after imaging vs. those with lower AmygA ( P =0.028). Conclusion: Higher AmygA associates with an increased risk for TTS among a retrospective population with a high rate of malignancy. This heightened neurobiological activity is present years before the onset of TTS and may impact the timing of the syndrome. Accordingly, heightened stress-associated neural activity may represent a therapeutic target to reduce stress-related diseases, including TTS. Graphical Abstract: